Etika Berbahasa Indoensia Anak Usia Sekolah Dasar Kelas V SD Negeri 5 Watang Sidenreng - Kamal Kamal; Handy Ferdiansyah; Zulkifli N; Usman M; Agussalim Agussalim (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to describe the form of ethical speaking of the elemntary school age children in grade V and found the factors cause the less ethical language at primary school age children in grade 5 SD Watang Sidenreng. This study used qualitative descriptive approach. The sources of data obtained from the fifth grade students SD Negeri 5 Watang Sidenreng totaling 28 students. Data obtained by participant observation, in-depth interviews, the study documents, then treated with qualitative descriptive analysis. The results of this study indicate that a form of ethical language in class V can be analyzed in terms of words, sentences, phrases, intonation elements (suprasegmental), and kinesic elements. The factors determining the level of ethical or less ethical levels depend on several factors, namely (1) smooth rough words. (2) a short length utterance. (3) the order of the utterance. (4) intonation (suprasegmentl), and kinesic cues. (5) the use of the pharase marker. While the factors that lead to unethical language in class V, namely (1) friends direct criticize the harsh words, (2) being the most correct opinion, (3) intentionaly accuse opponents utterance, (4) intentionally criticize the opponent utterance, (5) intentionaly embarrass oppenents utterance, (6) giving bad names, (7) brag or boast, (8) being happy if friends misfortune, (9) using derect speech, and (10) has become a bad habit.